PERAN KOMUNITAS DOSEN DALAM PENINGKATAN KUALITAS PEMBELAJARAN DI PERGURUAN TINGGI - Abdul Sani; Annisa Regina Maharani; Nazimah (Jurnal Genta Mulia, 2025)
The quality of learning in higher education is the primary foundation for producing competent and competitive graduates. Various efforts have been made to improve it, one of which is through the formation and empowerment of lecturer communities. This article aims to examine in-depth the strategic role of lecturer communities in improving the quality of learning. Using comprehensive literature research methods, this article analyzes various studies and expert perspectives regarding the contribution of lecturer communities to the development of innovative pedagogy, the exchange of knowledge and experience, and collaboration in research and curriculum development. The results indicate that lecturer communities have significant potential as catalysts for positive change in learning practices, but their effectiveness depends heavily on institutional support, active member participation, and a clear focus on improving the quality of learning. This article concludes that strengthening and empowering lecturer communities is a crucial investment for the sustainable improvement of the quality of higher education.